Fuzzy Takagi-Sugeno Method in Microcontroller Based Water Tank System - Nur Maisarah Mohd Sobran; Munirah Mohd Salmi; Mohd Bazli Bahar; Md Nazri Othman; Siti Halma Johari (Institute of Advanced Engineering and Science, 2018)
This paper present the performance of Fuzzy logic controller in maintain level of water in water tank system. The mathematical modelling was developed to get the initial idea of the system performance. Later, the prototype of water tank system were constructed and tested to get the real time results. The Takagi-Sugeno “on” and “off” interference technique method was implemented due to the control limitation of the pump motor that being used in the experimental setup. The fuzzy logic controller was realized by embedded the algorithm in microcontroller of the water tank system. The experimental results show acceptable level of water within the range of 18cm to 20.5cm and settling time 59 seconds with 20 cm set point.